Meningkatkan Pendidikan Pipitak Jaya - Anida Anida; Najmi Hidayati; Maryanti Maryanti; Niswah Nur Najihah; Muhammad As'ad; Muhammad Ari Hidayat; Fithriana Syarqawie (Jalujur: Jurnal Pengabdian Masyarakat, 2022)
AbstractPipitak Jaya is one of the villages in the Piani sub-district, Rantau Regency, South Kalimantan Province. It is about 20 KM from the town of Rantau to get to the village of Pipitak Jaya. With this long distance, the village of Pipitak is also one of the backward villages. Langging behind in many ways, langging behind in network access, and in terms of education. Currently it is believed that education is an important thing that must be demanded by everyone because it is the the demands of the times that put educated people as a priority compared to the other way around. Facing educational problems in Pipitak Jaya Village, there are several strategies/ approaches taken to achieve change/ improvement in terms of education, with PAR (Participatory Action Research), ABCD (Asset Based Community development), and CBPR (Community Based Participatory Research) strategies. After carrying out several mentoring activities in terms of education, several positive changes occurred in the children of Pipitak Jaya Village, namely a more avtive and enthusiastic learning spirit, increased self-confidence, and of course more developed and advances understanding and knowledge.  AbstrakPipitak Jaya adalah salah satu desa yang ada di kecamatan Piani, Kabupaten Rantau Provinsi Kalimantan selatan . Kurang lebih 20km menempuh jarak dari kota Rantau agar dapat sampai ke desa Pipitak Jaya. Dengan jauhnya jarak tempuh ini membuat desa pipitak juga menjadi salah satu desa yang tertinggal. Tertinggal dalam berbagai hal, tertinggal dalam akses jaringan, dan segi pendidikan. Saat ini diyakini bahwa pendidikan merupakan hal penting yang harus dituntut bagi setiap orang karena merupakan tuntutan zaman yang meletakkan orang berpendidikan menjadi lebih prioritas dibandingkan sebaliknya. Menghadapi permasalahan pendidikan di Desa Pipitak Jaya, ada beberapa strategi /pendekatan yang dilakukan untuk mencapai perubahan/peningkatan dari segi pendidikan, dengan strategi PAR (Participatory Action Research), ABCD (Asset Based Community Development), dan CBPR (Community Based Participatory Research). Setelah melakukan beberapa kegiatan pendampingan dari segi pendidikan, didapatkan beberapa perubahan positif yang terjadi pada anak-anak Desa Pipitak Jaya yaitu semangat belajar yang lebih giat dan antusias, tingkat kepercayaan diri lebih meningkat, dan tentunya pemahaman dan pengetahuan yang lebih berkembang dan maju.